The Effect of Video-Based Learning on Elementary Students’ Learning Outcomes in Ecosystem Topics - Jasum Novi Daria; Sri Sumarni; Makmum Raharjo (Jurnal Penelitian Pendidikan IPA, 2026)
Understanding ecosystems is not only academically important but also practically valuable in fostering environmental awareness. Knowledge of ecosystem balance can cultivate a sense of responsibility toward environmental conservation and sustainability. This study aims to examine the effect of interactive video-based learning on elementary school students’ learning outcomes in ecosystem topics. The research employed a Research and Development (R&D) approach using the ADDIE model and involved 30 fifth-grade students at SD Negeri Penuduan, Musi Banyuasin. Data were collected through expert validation, practicality testing, and pretest–posttest assessments, and were analyzed using N-gain scores and paired-sample t-tests. The validation results indicated that the developed learning videos were categorized as “very valid” in terms of content, language, and media aspects, with an average practicality level exceeding 90%. The pretest results showed an initial average score of 38, while the posttest average increased to 86.67, with an N-gain score of 0.78, which falls into the “high” category. The paired-sample t-test revealed a statistically significant improvement in students’ learning outcomes (p < 0.05). These findings provide empirical evidence that interactive video-based learning is effective in improving elementary school students’ learning outcomes and their understanding of ecosystem concepts.